Pengaruh Gaya Kepemimpinan Demokratis Kepala Sekolah dan Motivasi Kerja Guru terhadap Prestasi Belajar Peserta Didik SMP - Astuti Astuti; Wildan Wildan; Bahtiar Bahtiar (Schemata: Jurnal Pasca Sarjana IAIN Mataram, 2021)
This study aims to: 1) Find the influence of the principal's democratic leadership style on students' learning achievement. 2) Finding the effect of teacher's working motivation on students' learning achievement. 3) Discover the influence of the principal's democratic leadership style and teacher's working motivation on student learning achievement. This research uses a quantitative approach with data collection techniques using questionnaires and documentation. The data analysis technique uses simple linear regression and multiple linear regression which is calculated using SPSS 21. The results of the calculation of simple linear regression are: 1) There is an influence of democratic leadership style on students' learning achievement based on sig values of 0,000<0,05 and the calculated t value of 4,823>2,028 and the effect of variable X1 on Y by 39,2%. 2) There is an influence of teacher work motivation on student achievement based on sig. amounted to 0,001<0,05 and the t value of 3,759>2,028 and the influence of X2 on Y was 28,2%. 3) The results of the calculation of the multiple linear regression test that there is an influence of the democratic leadership style of the principal and the work motivation of teachers together on student learning achievement based on sig values of 0,000<0,05 and the value of F value of 21,198>3,26 and the magnitude of the effect of X1 and X2 together against Y of 54,8%. Keywords: Democratic leadership style, teacher work motivation, student learning achievement. Penelitian ini bertujuan untuk: 1) Mengetahui pengaruh gaya kepemimpinan demokratis kepala sekolah terhadap prestasi belajar siswa. 2) Mengetahui pengaruh motivasi kerja guru terhadap prestasi belajar siswa. 3) Mengetahui pengaruh gaya kepemimpinan demokratis kepala sekolah dan motivasi kerja guru terhadap prestasi belajar siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik pengumpulan data menggunakan angket dan dokumentasi. Teknik analisis data menggunakan regresi linier sederhana dan regresi linier berganda yang dihitung dengan bantuan program SPSS 21. Hasil perhitungan regresi linier sederhana adalah: 1) Terdapat pengaruh gaya kepemimpinan demokratis terhadap prestasi belajar siswa berdasarkan nilai sig 0,000<0,05 dan nilai t hitung sebesar 4,823>2,028 serta pengaruh variabel X1 terhadap Y sebesar 39,2%. 2) Ada pengaruh motivasi kerja guru terhadap prestasi belajar siswa berdasarkan sig. sebesar 0,001<0,05 dan nilai t hitung sebesar 3,759>2,028 serta pengaruh X2 terhadap Y sebesar 28,2%. 3) Hasil perhitungan uji regresi linier berganda bahwa terdapat pengaruh gaya kepemimpinan demokratis kepala sekolah dan motivasi kerja guru secara bersama-sama terhadap prestasi belajar siswa berdasarkan nilai sig 0,000<0,05 dan nilai nilai F sebesar 21.198 > 3,26 dan besarnya pengaruh X1 dan X2 secara bersama-sama terhadap Y sebesar 54,8%. Kata kunci: Gaya kepemimpinan demokratis, motivasi kerja guru, prestasi belajar siswa.